파키스탄 신드주의 밀 재배지역 생산량과 기후자료와의 상관분석 - 고정훈; 장동호 (기후연구, 15(2), 2020)
This study investigated the relationship analysis between wheat cultivated area and the climate data in Sindh province of Pakistan. The extraction of wheat cultivation area is detected using the remote sensing technique. The analysis of the study area reveals the annual mean maximum and the mean minimum temperature tends to risen with a large range of changes. The trend of average annual precipitation showed a large change, thus it was confirmed that the increase and decrease yield of wheat were depend on the various growth periods of wheat crop. The most influential factors are the annual mean precipitation and the annual mean minimum temperature at the seedling stage of wheat crop. The annual precipitation, annual mean maximum, and the annual mean minimum temperature are significant at the growth period. The annual mean maximum and the annual mean minimum temperatures are significant during the ripening stage of wheat crop in the study area. The results of the study showed that wheat production varies with climate change in the Sindh province. In addition, this study will be used as an important basis for solving crop cultivation areas and production problems caused by climate change in the region. KCI Citation Count: 1